The problems of delimitation of the EEZ between Taiwan and the Philippines: with special reference to the legality of their claims - Sun, Kuan-Ming (Centre for Law and Society, 2026)
[After the extension of the maritime zones of littoral states in the 1970s and in the beginning of 1980s, 1 the South China Sea came into the limelight as a disputed area. Legally speaking, the South China Sea is a semi-closed sea. 2 Geographically speaking, its physical location is 'further complicated by the present politiGal situation. The area is complicated by the presence of political blocs, 3 ideological confrontation4 and the special legal status of Taiwan. 5 Though the area as a whole is known to be a troublesome one, there are few people who pay sufficient attention to the north-east corner where a serious fishery dispute has arisen between the Republic of Philippines and the Republic of China (Taiwan). The reasons for such inadvertence may be the following. Firstly T~iwan is not a member state of the United Nations and most states consider that it is part of the Chinese People's Republic (CPR). Hence, this dispute should be one between CPR and the Philippines. Secondly unlike the military conflict between CPR and Vietnam over ~the sovereignty of the Four Claim Area, 6 there is no such drastic confrontation between the Philippines and Taiwan. The passive attitude of Taiwan toward the dispute makes the entire situation even less clear. 7